Congenital Oropouche in Humans: Clinical Characterization of a Possible New Teratogenic Syndrome - Bethânia de Freitas Rodrigues Ribeiro; André Rodrigues Façanha Barreto; André Pessoa; Raimunda do Socorro da Silva Azevedo; Flávia de Freitas Rodrigues; Bruna da Cruz Beyruth Borges; Natália Pimentel Moreno Mantilla; Davi Dantas Muniz; Jannifer Oliveira Chiang; Lucas Rosa Fraga; Fernanda Sales Luiz Vianna; Maria Teresa Vieira Sanseverino; et al. (Viruses)
Oropouche fever is caused by the Oropouche virus (OROV; Bunyaviridae, Orthobunyavirus), one of the most frequent arboviruses that infect humans in the Brazilian Amazon. This year, an OROV outbreak was identified in Brazil, and its vertical transmission was reported, which was associated with fetal death and microcephaly. We describe the clinical manifestations identified in three cases of congenital OROV infection with confirmed serology (OROV-IgM) in the mother-newborn binomial. One of the newborns died, and post-mortem molecular analysis using real-time RT-qPCR identified the OROV genome in several tissues. All three newborns were born in the Amazon region in Brazil, and the mothers reported fever, rash, headache, myalgia, and/or retro-orbital pain during pregnancy. The newborns presented with severe microcephaly secondary to brain damage and arthrogryposis, suggestive of an embryo/fetal disruptive process at birth. Brain and spinal images identified overlapping sutures, cerebral atrophy, brain cysts, thinning of the spinal cord, corpus callosum, and posterior fossa abnormalities. Fundoscopic findings included macular chorioretinal scars, focal pigment mottling, and vascular attenuation. The clinical presentation of vertical OROV infection resembled congenital Zika syndrome to some extent but presents some distinctive features on brain imaging and in several aspects of its neurological presentation. A recognizable syndrome with severe brain damage, neurological alterations, arthrogryposis, and fundoscopic abnormalities can be associated with in utero OROV infection.